Bio Analytical Method Development Of an Anti-HIV-1 Drug Efavirenz Using High Performance Liquid Chromatography In Human Plasma. (2017) - Deepakumari, H.N.; Mallegowda, S.M.; Prashanth, M.K.; Revanasiddappa, H.D.
Abstract: A highly sensitive, selective and validated high performance liquid chromatography (HPLC) method has been developed for the quantitative determination of efavirenz in human CPDA plasma. The analyte and internal standard (IS) duloxetin (DXT) were extracted from human plasma using liquid-liquid extraction technique, then separated on a BDS hypersil C18 (15cm, 4.6mm x 5μm), reverse phase column using a mobile phase comprising of acetonitrile and 50 mM sodium dihydrogen orthophosphate solution (pH 5.5) (48:52, v/v) and column oven temperature was maintained at 30 °C. It was pumped at a flow rate of 0.8 mL/min with an injection volume of 15 µL, with a total run time of 15 min. The detection was performed on a tandem mass spectrometer equipped with electro spray ionization (ESI) source. Calibration curve for EFZ was linear within the selected range of 0.03–4.57 µg/mL in human plasma with mean correlation coefficient of 0.999. The LLOQ for efavirenz was found to be 0.03 µg/mL. The intra- and inter-assay precision and accuracy of the quality control samples, expressed as the percent relative standard deviation (% RSD) was less than 2%. The mean recovery was 96.63% to 112.71%, for EFZ and DXT, respectively. This method has been demonstrated to be an improvement over existing methods due to its greater sensitivity and specificity. The data obtained show that the sensitivity and selectivity of this method are adequate for drug monitoring in clinical research and pharmacokinetic investigation of EFZ